Taxonomic review and cladistic analysis of Neotropical spider genus Epicratinus Jocqué & Baert, 2005 (Araneae: Zodariidae) with description of eleven new species - Gonçalves, Ricardo Antonio; Brescovit, Antonio Domingos (Zootaxa, 2020)
A taxonomic revision and phylogenetic analysis of the spider genus Epicratinus Jocqué & Baert, 2005 is presented. The phylogenetic analysis is based on a data set including 16 Epicratinus species plus 9 outgroups representing by five related zodariid genera and one of them considered most basal as the root. These taxa were scored for 49 morphological characters. Parsimony was used as the optimality criterion and a sensitivity analysis was performed using different character weighting concavities. Five unambiguous synapomorphies support the monophyly of Epicratinus. Some internal clades within the genus are well-supported and their relationships are discussed. Epicratinus includes 16 species, all with males and females. A species identification key and distribution maps are provided for all. New morphological data are also presented for five previously described species. All 16 species occur only in the New World. The following species are transferred to Epicratinus: E. perfidus (Jocqué & Baert), comb. nov. from Tenedos; Epicratinus perfidus Jocqué & Baert comb. nov. and newly synonymized with E. santacruz Grismado & Izquierdo and this last species is treated as the junior synonym. Epicratinus petropolitanus (Mello-Leitão) has the male described for the first time. The following 11 species are newly described as new: E. zangief sp. nov.; E. pegasus sp. nov.; E. pikachu sp. nov.; E. stitch sp. nov.; E. ehonda sp. nov.; E. anakin sp. nov.; E. vader sp. nov.; E. omegarugal sp. nov.; E. zelda sp. nov.; E. dookan sp. nov. and E. mauru sp. nov., all from Brazil.